Porcine Platelet von Willebrand Antigen II (vW AgII): Inhibitory Effect on Collagen-induced Aggregation and Comparative Distribution with Human Platelets - Royo, Teresa; Vidal, Matilde; Badimon, Lina (Thrombosis and Haemostasis, 1998)
Von Willebrand factor (vWF) is synthesized by human endothelial cells and megakaryocytes as a large precursor, the pre-provWF, which is finally cleaved into the propolypeptide of vWF (pp-vWF) and the mature vWF. We have purified in parallel the pp-vWF and the GP IIb-IIIa from porcine platelets. The N-terminus comparative analysis of porcine pp-vWF with respect to other species revealed more than a 75% and 65% homology with the bovine and human pp-vWF, respectively. Purified pp-vWF inhibited collagen-induced platelet aggregation in porcine platelet rich plasma (PRP) and specifically binds to collagen. Polyclonal antibody pabBp19 against the purified protein was prepared and characterized by ELISA, Western-blot and immunocytochemistry. The distribution of pp-vWF in soluble and membrane fractions from pig platelets has been performed by immunolabeling detection. pabBp19 did not blot human platelet lysates but human pp-vWF was detectable using the antibody Frieda 013091. Cell distribution and quantification studies of human and porcine platelet pp-vWF showed that the protein exists in the soluble and membrane fractions and its pattern is similar in both species.